Science of scaling research agenda for the CGIAR Regional Integrated Initiative for Diversification in East and Southern Africa (Ukama Ustawi) - Schut, Marc; Mugambi, Samuel (Wageningen University & Research, 2022)
Finding out how to successfully scale technological innovations (e.g. crop varieties, fertilizer, machines) and non-technological innovations (e.g. knowledge on how to access finance, policies and partnership models) is high on the agendas of researchers, practitioners and policy makers involved in agricultural development. However, scaling innovations is not so straightforward. It is a complex and political process where bottlenecks for scaling innovation are often context or country specific. There is a lot that we do not know yet about how innovations scale can be supported. Science of scaling offers a new academic field that is concerned with addressing these scaling knowledge gaps. Twenty-nine (29) experts working in the east and southern Africa region shared their views on key opportunities and bottlenecks for scaling, that informed a science of scaling research priorities.